Search fields for radical innovations involving market research - Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2001)
Strong market orientation is essential for innovation success! Although both academics and market research practitioners would generally accept this statement, alignment with the needs of the customer often results in conservative innovation strategies. Due to their focus on what is currently on offer in the marketplace, customers primarily demand so-called incremental innovations. Companies however, want to develop entry points for radical innovations. The identification of radical innovations is a difficult task whose implementation is often associated with significant risk. It is questionable if market research can alone allow innovation management to develop attractive search fields for radical innovations and if it can also contribute to the reduction of the risk that such innovations inherently possess. Closer observation shows that the market research methods used today for the discovery of radical innovations in the form of new market/technology combinations possess only limited suitability. Empirical tests verify that success-fully innovative companies often don't use such methods, rather they involve specifically qualified, innovative knowledge carriers early-on in the process such as Lead Users or external experts with relevant knowledge from analogous markets in the search for innovations. When searching for applications for radical innovations, market researchers should initially concentrate on the question of who they address as the information source. How successful the process of involving experts is and how well supported through the methodology it is, depends heavily on the specific factors and conditions related to the pro-ject planning.
urn:nbn:de:gbv:830-opus-1536
Keywords: 650; Produktentwicklung; Produktinnovation; Marktforschung